Rethinking the Causes of Moral Decline from the Perspectives of the Bible and the Qur’ān - Abdelgalil, Reda (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2025)
This study explores the essential causes of human’s moral decline as presented in the Bible and the Qur’ān. Applying a thematic comparative approach supported by textual analysis, this article seeks to explore the shared themes, parallels and scriptural visions of the key causes of moral decline. By analyzing key passages, the article highlights how both scriptures identify the timeless essential four factors of recurring moral decline—Satan, envy, anger, and lying. These four elements serve as roots behind many modern ethical crises, distorting the moral fabric of human behavior in contemporary societies. While many empirical and applied studies address the external symptoms of moral decline, this study aims to examine its key causes from a theological and scriptural perspective. Drawing upon the ethical framework of both the Bible and the Qur’ān, the study highlights how these divine texts diagnose the roots of human moral failure and offer solutions for humanity to regain its instinctual purity and live in peace and prosperity. The study’s findings demonstrate the shared moral wisdom of Christian and Islamic traditions, emphasizing that identifying and understanding the deep-rooted causes of moral decline within the framework of the divine guidance of the Bible and the Qur’ān represents a vital necessity for resolving contemporary ethical challenges in an increasingly fragmented world. The study thus contributes to the interfaith moral discourse and opens avenues for further studies on addressing ethical issues of the modern context.